2021
DOI: 10.1002/adfm.202008395
|View full text |Cite
|
Sign up to set email alerts
|

Step‐By‐Step Atomic Insights into Structural Reordering from 2D to 3D MoS2

Abstract: Vertically stacked low‐dimensional heterostructures are outstanding systems both for exploring fundamental physics and creating new devices. Due to nanometer‐scale building blocks, atomic scale phenomena become for them of fundamental importance, including during device operation. These can be accessed in situ in aberration‐corrected scanning transmission electron microscopy (STEM) experiments. Here, the dynamics of a graphene‐MoS2 heterostructure are studied under Joule heating, where the graphene serves as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Controlling particle morphology is of great importance to many industries including semiconductors, nanomaterials, and steel fabrication. Levlev et al showed that a mechanistic understanding of nucleation and growth mechanisms can lead to improved modeling of material properties and future material discovery . In the nuclear industry, particle morphology can impact the environmental transport of uranium, nuclear fuel performance in reactors, long-term storage of spent nuclear fuel, and support nuclear forensics and nuclear safeguards in identifying the processing history of nuclear materials. ,, Prior studies have identified many variables including pH, temperature, reaction time, and calcination temperature that impact the final particle morphology. Advancements in particle segmentation and machine learning enable quantification of even subtle morphology changes. , The challenge, however, has been in understanding the fundamental principles that result in unique particle morphologies based on the chemical and physical processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling particle morphology is of great importance to many industries including semiconductors, nanomaterials, and steel fabrication. Levlev et al showed that a mechanistic understanding of nucleation and growth mechanisms can lead to improved modeling of material properties and future material discovery . In the nuclear industry, particle morphology can impact the environmental transport of uranium, nuclear fuel performance in reactors, long-term storage of spent nuclear fuel, and support nuclear forensics and nuclear safeguards in identifying the processing history of nuclear materials. ,, Prior studies have identified many variables including pH, temperature, reaction time, and calcination temperature that impact the final particle morphology. Advancements in particle segmentation and machine learning enable quantification of even subtle morphology changes. , The challenge, however, has been in understanding the fundamental principles that result in unique particle morphologies based on the chemical and physical processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The first paper on inter-layer vacancy migration appeared in 2014 for multilayer graphene. 24 In the case of TMDCs, both theoretical and experimental evidence have been presented recently to show heat-induced migration of S-, 25 or Se-vacancies 26 in the respective metal chalcogenides. Regarding other semiconductors, a defect migration process was reported for TiO 2 , where the number of surface oxygen vacancies increased on Pt-decorated TiO 2 by migration of bulk vacancies to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] For in situ biasing of 2D materials, relevant research is hardly found in the literature. [40][41][42][43][44] Herein, we focus on the structural evolution of a suspended MoS 2 device under high bias conditions through an advanced in situ technique. Fan et al have studied the electrical breakdown of tungsten disulfide (WS 2 ), and examined the results of mono-and fewlayer samples.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Inani et al have fabricated the graphene/MoS 2 heterostructure and investigated its dynamic behavior induced by Joule heating, which takes place mainly in graphene, then transfers some of the heat to the MoS 2 similar to a hot plate. [44] In this work, we expect to verify the effect of bias on the material damage by investigating the in situ results at different voltages and the ex situ results. With the help of microelectromechanical system (MEMS) technology, we are able to create a lab-on-achip biasing environment for real-time observation.…”
Section: Introductionmentioning
confidence: 99%